The Nexus of Audit Quality and Fraud Prevention: Evidence from Buleleng Inspectorate - Fristamara, Yosep; Pradnyawati, Ni Luh Putu Eka; Werastuti, Desak Nyoman Sri; Purnamawati, I Gusti Ayu; Sinarwati, Ni Kadek (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to examine how auditor competence, supervisory independence, and internal control systems influence internal audit quality and fraud prevention in Indonesia's public sector, with particular focus on the moderating role of auditor integrity in shaping the effectiveness of these oversight mechanisms. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), this study analyzes data from 53 auditors at the Buleleng Regency Inspectorate to test six direct relationships and six moderating effects of auditor integrity on internal audit quality and fraud prevention. The study reveals three key findings. First, all direct effects prove significant: internal control systems emerge as the strongest predictor of internal audit quality (β=0.431, p<0.001), while auditor competence most powerfully influences fraud prevention (β=0.408, p=0.001). Second, auditor integrity exhibits complex and counterintuitive moderation patterns: it negatively moderates the competence-audit quality relationship (β=-0.264, p=0.034) and independence-audit quality relationship (β=-0.095, p=0.029), indicating compensatory mechanisms or contextual pressures in corrupt environments. Third, integrity does not moderate any relationships with fraud prevention nor internal control system relationships with either outcome, revealing that fraud prevention is more heavily determined by structural factors than individual ethical characteristics.